Eccrine Porocarcinoma of the Skin is Rising in Incidence in the East of England - Goon, Peter K.C.; Gurung, Puran; Levell, Nicholas J.; Subramanian, Priya; Yong, Adrian Sze Wai; Lee, Kevin Y.C.; Igali, Laszlo; Greenberg, David; Shah, Syed Nasir; Tan, Eunice (Society for Publication of Acta Dermato-Venereologica, 2018)
[No abstract available]